Surveillance of mosquitoes (Diptera: Culicidae) in Rajshahi, Bangladesh - Anik, Md Tanvir Anjum; Farjana, Thahsin (Research in Agriculture Livestock and Fisheries, 2019)
Mosquitoes are considered the most important arthropod vectors in the world. Mosquito borne diseases are major public health problems in most of tropical and subtropical countries. An investigation was performed at Bagha upazila in Rajshahi district to identify the mosquito species and their breeding sites at the study area. Adult mosquitoes were collected by insect collecting net, light traps and human bait method and larvae were collected by dipper, mug, ladle spoon and dropper. A total of 1947 adult mosquitoes and 1376 larvae were collected and identified. Total ten species of adult mosquitoes and nine species of larvae under two genera were identified. The collected mosquitoes were belonging to two genera- Anopheles (An.) and Culex (Cx.). The identified species were Cx. quinquefasciatus, Cx. bitaeniorhynchus, Cx. tritaeniorhynchus, Cx. gelidus, Cx. pseudovishnui, Cx. whitmorei, Cx. fuscanus, Cx. fuscocephala, An. aconitus, An. vagus and An. barbirostris. In both cases of larvae and adult mosquitoes, Culex was found more prevalent than Anopheles. In case of larvae the prevalence was 75.8% and 24.2%, and in case of adult it was 71.2% and 28.8% for Culex and Anopheles, respectively. Among the all identified mosquitoes, Cx. quinquefasciatus showed the highest abundance in both cases of larval (23.5%) and adult mosquitoes (25.2%). From the survey it has been apparent that the Culex species may prefer the polluted water bodies in the locality like households, dairy sheds and drains whereas Anopheles species may prefer agricultural fields, and dairy sheds. This study will help to detect the breeding sites of mosquitoes in study areas and to take necessary steps to control mosquitoes and mosquito borne diseases. Res. Agric., Livest. Fish.6(2): 329-336, August 2019